Determination of labile barium in petroleum-produced formation water using paper-based DGT samplers - de Oliveira, Wellington [UNESP]; Batista de Carvalho, Maria de Fatima; de Almeida, Eduardo; Menegario, Amauri Antonio [UNESP]; Domingos, Roberto Naves [UNESP]; Brossi-Garcia, Ana Luiza [UNESP]; do Nascimento Filho, Virgilio Franco [UNESP]; Santelli, Ricardo Erthal (Elsevier B.V., 2012)
A polyacrylamide hydrogel containing the Chelex-100 resin has traditionally been used as the binding agent for the diffusion gradients in thin films (DGT) technique. The Chelex-100 resin, although important for the determination of various transition metals, is unsatisfactory for the determination of alkaline earth metals, particularly Ba. In this paper, a cellulose membrane, treated with phosphate (P81 membrane), was evaluated as a binding agent for DGT devices for the determination of Ba in produced formation water (PEW) samples. In addition, diffusive layers of filter paper (cellulose) were tested to diffuse Ba through the DGT devices. Experiments to evaluate the key variables of the technique (pH, deployment time, and ionic strength/salinity) were performed. The Ba sampled by these DGT devices was measured using inductively coupled plasma optical emission spectrometry. Aiming to generate information (related to bioavailability of Ba) on the reuse of PEW for irrigation, the determination of Ba in onshore and offshore samples was performed. The new approach was effective for determination of Ba in onshore samples. To determine Ba in offshore samples, it was necessary to use an alternative calibration procedure due to the high NaCl concentration in these samples. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Produced formation water; DGT; Barium; P81 membrane; Fractionation; Speciation